2013
DOI: 10.1186/1471-2164-14-878
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two putative reference genes from grapevine suitable for gene expression analysis in berry and related tissues derived from RNA-Seq data

Abstract: BackgroundData normalization is a key step in gene expression analysis by qPCR. Endogenous control genes are used to estimate variations and experimental errors occurring during sample preparation and expression measurements. However, the transcription level of the most commonly used reference genes can vary considerably in samples obtained from different individuals, tissues, developmental stages and under variable physiological conditions, resulting in a misinterpretation of the performance of the target gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 55 publications
2
47
0
Order By: Relevance
“…For non-model plant species, the reference genes are mainly identified by the search for orthologous sequences of common housekeeping genes reported in model plant species, due to limited genetic and sequence information (Gonzalezaguero et al, 2013). However, numerous studies have reported that the expression levels of traditional housekeeping genes vary considerably alterations in different biological sample and variable experimental condition (Hu et al, 2009; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For non-model plant species, the reference genes are mainly identified by the search for orthologous sequences of common housekeeping genes reported in model plant species, due to limited genetic and sequence information (Gonzalezaguero et al, 2013). However, numerous studies have reported that the expression levels of traditional housekeeping genes vary considerably alterations in different biological sample and variable experimental condition (Hu et al, 2009; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, RNA-seq has emerged as a powerful high-throughput technology used for transcriptome analysis in different organisms and treatments3940414243. In spite of being a technique used for many years, RNA-seq data has been used in the plant research field for the selection and validation of new and more robust RT-qPCR reference genes only in grape, soybean and Lycoris 444546.…”
mentioning
confidence: 99%
“…Suitable reference genes for each experimental set should be identified independently. In grapevine, reference genes have been evaluated for different varieties [31], developmental stages [14], and physiological conditions [4], such as biotic and abiotic stress. This need to optimize reference genes for different conditions arises in studies of other plants, such as rice [18,30,45], potato [27,40], apple [5,21], and strawberry [12].…”
Section: Introductionmentioning
confidence: 99%